2020
DOI: 10.1002/adfm.202002638
|View full text |Cite
|
Sign up to set email alerts
|

Blocking of Conducting Channels Widens Window for Ferroelectric Resistive Switching in Interface‐Engineered Hf0.5Zr0.5O2 Tunnel Devices

Abstract: Films of Hf 0.5 Z 0.5 O 2 (HZO) contain a network of grain boundaries. In (111) HZO epitaxial films on (001) SrTiO 3, for instance, twinned orthorhombic (o-HZO) ferroelectric crystallites coexist with grain boundaries between o-HZO and a residual paraelectric monoclinic (m-HZO) phase. These grain boundaries contribute to the resistive switching response in addition to the genuine ferroelectric polarization switching and have detrimental effects on device performance. Here, it is shown that, by using suitable n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 48 publications
(74 reference statements)
3
27
0
Order By: Relevance
“…Moreover, whereas two critical ( V + C-LOW and V + C-HIGH ) fields, related to polarization reversal and ionic motion, respectively, were observed in LSMO/BTO junctions, only the V + C-LOW remains apparent in the R ( V W ) loops of the LSMO/STO/BTO hybrid junctions. This observation confirms that the STO layer contributes to suppress the ionic channel and the HRS ION state 64 (Supplementary Note 18 and Supplementary Fig. 18 ).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Moreover, whereas two critical ( V + C-LOW and V + C-HIGH ) fields, related to polarization reversal and ionic motion, respectively, were observed in LSMO/BTO junctions, only the V + C-LOW remains apparent in the R ( V W ) loops of the LSMO/STO/BTO hybrid junctions. This observation confirms that the STO layer contributes to suppress the ionic channel and the HRS ION state 64 (Supplementary Note 18 and Supplementary Fig. 18 ).…”
Section: Resultssupporting
confidence: 78%
“…This enhancement results from the larger asymmetry of the electronic potential profile across the device. A similar approach had been used earlier to improve ER in ferroelectric tunnel barriers 9,64 . Moreover, whereas two critical (V + C-LOW and V + C-HIGH ) fields, related to polarization reversal and ionic motion, respectively, were observed in LSMO/BTO junctions, only the V + C-LOW remains apparent in the R(V W ) loops of the LSMO/STO/BTO hybrid junctions.…”
Section: Resultsmentioning
confidence: 99%
“…Electroresistance (ER) loops were soon measured in epitaxial HZO films a few nanometers thick. 76,81,83,87 Sulzbach et al 87 reported electroresistance loops with the same coercive voltage (Figure 13a) than the corresponding polarization loops (Figure 13b), indicating the close relation between ferroelectric switching and electroresistance. The Brinkman model was used to fit I-V characteristics pointing to tunneling current as predominant conduction mechanism.…”
Section: Devicesmentioning
confidence: 77%
“…Thus, genuine tunneling ER resulting from ferroelectric switching can be accompanied by ER resulting from other transport mechanisms. They are associated to ions motion, and cause huge ER values up to 10 5 % 87 or even 10 6 %. 83 Noheda and coworkers 83,86 proposed that the huge ER is connected to oxygen vacancy migration between bottom LSMO electrode and HZO film.…”
Section: Devicesmentioning
confidence: 99%
“…Accordingly, FTJ performance could be drastically improved. 117 The benefit of single layer stacks 118 is the low non-polar interface layer thickness generating lower depolarization fields and an improved retention behavior. In contrast, the low barrier thickness causes only about 100 field cycles before breakdown and a high FTJ capacitance, which makes the tunnel current difficult to read by the sensing circuit.…”
Section: Outlook On Emerging Ferroelectric Devicesmentioning
confidence: 99%